A THE UTILISATION OF TRADITIONAL HOUSE MEDIA AS CULTURALLY RELEVANT PEDAGOGY IN PROJECT-BASED LEARNING OF ELECTRON CONFIGURATION CHEMISTRY IN EAST NUSA TENGGARA - Yanti R. Tinenti; Hironimus Tangi; Theresia Wariani; Visensia H. B. Hayon; Ilidio X. Moreira (Jurnal Penelitian Pendidikan IPA, 2025)
The research question is: How are traditional Timorese houses utilised as a medium for teaching chemistry, and what are the implications, challenges, and impacts? The objective of this study is to investigate the use of traditional Timorese houses as a project-based learning medium for the topic of electron configuration, which has not been extensively explored in the Nusa Tenggara Timur region. The research method employed is a qualitative approach with a case study design. Data analysis was conducted using thematic analysis through six systematic stages. The findings of this study are as follows: Traditional Timorese houses: a). Can be utilised as a medium for chemistry education. b). They have a symbolic relationship with electron configuration material in terms of spatial layout and the number of occupied electron shells. c). Challenges require extra time in guiding students and implementing projects according to their objectives. d). The impact on teachers is to teach students collaboratively between schools and communities, encourage students to be more proactive and innovative, and support school accreditation. The impact on students includes: improved learning outcomes, motivation, critical thinking, and social awareness, becoming more proactive, as well as students' understanding of the material and home culture.